2012
DOI: 10.1037/a0027485
|View full text |Cite
|
Sign up to set email alerts
|

Eye movements of second language learners when reading spaced and unspaced Chinese text.

Abstract: The effect of spacing in relation to word segmentation was examined for four groups of non-native Chinese speakers (American, Korean, Japanese, and Thai) who were learning Chinese as second language. Chinese sentences with four types of spacing information were used: unspaced text, word-spaced text, character-spaced text, and nonword-spaced text. Also, participants' native languages were different in terms of their basic characteristics: English and Korean are spaced, whereas the other two are unspaced; Japane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 52 publications
8
46
0
Order By: Relevance
“…A final characteristic of Chinese that makes it visually distinct from Finnish and English, is that Chinese is an unspaced language, that is, there are no spaces between the words in Chinese sentences. The lack of word spacing in character-based languages has been shown to be very important in relation to eye movements, saccadic targeting and reading (see Bai, Yan, Liversedge, Zang, & Rayner, 2008;Blythe, Liang, Zang, Wang, Yan, Bai & Liversedge, 2012;Li, Liu & Rayner, 2011;Sainio, Hyönä, Bingushi & Bertram, 2007;Shen, Liversedge, Tian, Zang, Cui, Bai, Yan, & Rayner, 2012;Yan, Kliegl, Richter, Nuthmann & Shu, 2010;Zang, Liang, Bai, Yan & Liversedge, 2012). The lack of spaces between words in Chinese contributes further to its reduced horizontal extent, and this also means that a process of word segmentation is required for word identification to occur that is unnecessary in English and Finnish (with the exception of long, multimorphemic compound words, Bertram, Pollatsek, & Hyönä, 2004).…”
Section: ! 8!mentioning
confidence: 99%
“…A final characteristic of Chinese that makes it visually distinct from Finnish and English, is that Chinese is an unspaced language, that is, there are no spaces between the words in Chinese sentences. The lack of word spacing in character-based languages has been shown to be very important in relation to eye movements, saccadic targeting and reading (see Bai, Yan, Liversedge, Zang, & Rayner, 2008;Blythe, Liang, Zang, Wang, Yan, Bai & Liversedge, 2012;Li, Liu & Rayner, 2011;Sainio, Hyönä, Bingushi & Bertram, 2007;Shen, Liversedge, Tian, Zang, Cui, Bai, Yan, & Rayner, 2012;Yan, Kliegl, Richter, Nuthmann & Shu, 2010;Zang, Liang, Bai, Yan & Liversedge, 2012). The lack of spaces between words in Chinese contributes further to its reduced horizontal extent, and this also means that a process of word segmentation is required for word identification to occur that is unnecessary in English and Finnish (with the exception of long, multimorphemic compound words, Bertram, Pollatsek, & Hyönä, 2004).…”
Section: ! 8!mentioning
confidence: 99%
“…Bai, Yan, Liversedge, Zang, and Rayner (2008) found that while inserting spaces between words did not facilitate or interfere with reading, inserting spaces between characters did interfere with reading. Later studies showed that inserting spaces between words could help beginning readers of Chinese to read more efficiently and to learn new words (Blythe et al, 2012; Shen et al, 2012). Moreover, other studies found that reading speed was slowed down when Chinese readers could not view two characters belonging to a word simultaneously compared when they could do so (Li, Gu, Liu, & Rayner, in press; Li, Zhao, & Pollatsek, 2012).…”
mentioning
confidence: 99%
“…This does not mean that word boundaries are not important in Chinese reading. Indeed, a number of studies have shown that Chinese words play a very important role in reading and that words have psychological reality in Chinese (Bai, Yan, Liversedge, Zang, & Rayner, 2008; Hoosain, 1992; Li, Gu, Liu, & Rayner, 2013; Li, Bicknell, Liu, Wei, & Rayner, in press; Shen et al, 2012; Zang, Liang, Bai, Yan, & Liversedge, 2012) suggesting that word segmentation is necessary in Chinese reading. Without interword spaces, Chinese readers have to depend on high-level information to segment words.…”
mentioning
confidence: 99%